Penerapan Pembelajaran Berbasis Teori Bruner Melalui Representasi Enaktif, Ikonik, dan Simbolik untuk Meningkatkan Hasil Belajar Pecahan Berbeda Penyebut Siswa Kelas V Sekolah Dasar - Nur Fauziah, Nahdiah; Alvi Syafa`atu Rosidah; Muhammad Ma`dinul In`am Al Kamil; Umi Farihah; Indah Wahyuni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to improve students’ learning outcomes in the subject of addition and subtraction of fractions with different denominators through the application of Bruner’s Theory, specifically the enactive, iconic, and symbolic stages. This study employs the Classroom Action Research (CAR) design based on the Kemmis and McTaggart model, conducted over two cycles with a sample of 26 fifth-grade elementary school students. Data collection techniques included observation, documentation, and achievement tests, while data analysis was conducted both quantitatively and qualitatively. The results indicate a significant improvement in student learning outcomes, evidenced by an increase in the average score from 59.5 in the pre-intervention phase to 69.46 in Cycle I, and further to 82.19 in Cycle II, as well as a rise in mastery rates from 30.77% to 84.62%. These findings indicate that the systematic integration of the enactive, iconic, and symbolic stages of representation is capable of enhancing students’ conceptual understanding and procedural skills in fraction material. The novelty of this study lies in the explicit and systematic integration of Bruner’s stages of representation within the Classroom Action Research design for fractions with different denominators an area that has been rarely explored in depth in previous research. This study makes a theoretical contribution to the advancement of the constructivist approach and offers a practical contribution in the form of an applicable learning model designed to improve mathematics learning outcomes in elementary schools.